PJBL in Translation Course: What the English Department Students Learnt - Prastiwi, Chyntia Heru Woro; Wardhani, Norita Prasetya; Lestari, Mawar (IKIP PGRI Bojonegoro, 2026)
Project-Based Learning (PjBL) has really caught on in higher education. It gets students more involved and helps them pick up the crucial 21st-century skills. In terms of Translation course, research on how project-based activities actually impact students’ learning is still limited. We took a group of English Department students and had them create bilingual storybooks for kids as their project. The students translated stories they made from Indonesian to English and designed storybooks, paying close attention to language accuracy, cultural fit, and what young readers need. We investigated what the students actually got out of this experience, how it affected their learning, literacy, and life skills. Using a qualitative descriptive approach, we focused on the third-year students in a Translation course. We watched them in class, looked over the storybooks they made, and read their reflections on the project. They produced eleven bilingual storybooks, which we analyzed for recurring themes. This project really boosted the students’ critical thinking and creativity, especially when they had to solve tricky translation problems or tweak stories to fit a new audience. Working in groups made them better at collaborating and communicating as they had to negotiate and make decisions together. They sharpened their information, media, and tech skills by using digital tools and design platforms. The project helped them grow in other ways too, building flexibility, initiative, leadership, productivity, and social skills. Project-Based Learning is not just another teaching trend, it actually supports well-rounded learning in Translation courses for English Department students.